EFFECT OF MICRO-OSTEOPERFORATION ON THE RATE OF CANINE RETRACTION: A SPLIT-MOUTH RANDOMIZED CONTROLLED TRIAL - MANZOOR, M; AWAISI, ZH; AKHTAR, H (Biological and Clinical Sciences Research Journal, 2024)
Prolonged orthodontic treatment duration is a common clinical concern, prompting the exploration of minimally invasive techniques to accelerate tooth movement. Objective: This study aimed to evaluate the effect of micro-osteoperforations (MOPs) on the rate of canine retraction in orthodontic treatment and compare it with conventional techniques. Methodology: A split-mouth quasi-experimental trial was conducted at the Department of Orthodontics, Nishtar Institute of Dentistry, Multan, from June 2023 to December 2023. A total of 20 patients requiring maxillary canine retraction were included. One side of the maxillary arch received MOPs, while the contralateral side served as the control. Standard orthodontic mechanics were applied, and canine retraction was initiated using NiTi closed coil springs with [150 g] of force per side. The rate of canine retraction (mm/month) was measured at baseline and every four weeks using digital calipers on study casts. Secondary outcomes included anchorage loss, pain perception, and root resorption. Results: The mean canine retraction rate was significantly higher in the MOP group (1.71 ± 0.65 mm/month) compared to the control group (0.84 ± 0.21 mm/month) (p = 0.000). The mean retraction time was also significantly shorter in the MOP group (3.58 ± 1.17 months) than in the control group (7.59 ± 1.95 months) (p = 0.000). Younger patients (15–25 years) exhibited a significantly faster response to MOPs compared to older patients (26–30 years). Gender-based analysis showed that both male and female patients benefited from MOPs, but females exhibited a slightly higher retraction rate. The technique was more effective in Type I malocclusion compared to Type II. No significant adverse effects or complications were reported. Conclusion: MOPs significantly accelerate canine retraction, reducing overall orthodontic treatment duration. This technique serves as a minimally invasive adjunct to conventional treatment, improving efficiency while maintaining safety. Future research should focus on optimizing MOP parameters, patient-reported outcomes, and long-term stability.